PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR AL-QUR’AN PADA ANAK DI TPA SIDOMULYO KOTA PALANGKA RAYA - Satria Nur Rizki; Ajahari; Surawan (Institut Agama Islam Syubbanul Wathon Magelang, 2022)
This study aims to describe the role of parents in motivating children to learn the Qur'an in TPA Sidomulyo and the supporting and inhibiting factors. The research method uses descriptive qualitative methods with data collection techniques using observation and interviews. The subjects selected were parents who had children reading the Koran at the TPA using purposive sampling. Based on the selection of these subjects, 4 parents would be the main sources, and 3 children and 1 ustadz as informants. The results and discussion will describe the role of these parents. This research was conducted in Sidomulyo, Tumbang Tahai Village, Palangka Raya City. The results of this study found the role of parents in motivating their children to learn the Qur'an. The role of parents in motivating learning the Qur'an is influenced by several factors, namely supporting factors, 1) the will of the child, 2) the child's motivation, and 3) the environment, as well as inhibiting factors, 1) laziness, and 2) the busyness of parents.